LEARNER VARIABLES AND LANGUAGE ANXIETY IN ORAL COMMUNICATION: THE CASE OF UNIVERSITY STUDENTS IN THE PHILIPPINES - Ana Katrina Tapire Marcial (Informascope, 2016)
The study attempted to look into the relationship of language anxiety and specific learner characteristics of university students enrolled in an oral communication course at a university in the Philippines. Chi square test results showed that the level of anxiety of the learners had no significant relationship with gender but had significant relationships with their (a) selfperceived competence in using English, both for general aspects and for oral communication; (b) instances of English use outside the classroom, and (c) use of English at home. The study ends with the pedagogical implications and recommendations for teachers and learners in reducing or managing anxiety in the language classroom.